The Effect of Video-Based E-Learning and Interactive Quizzes on Learning Basic Electrical Concepts at SMKN 1 Ciruas - Rosiana, Enjel; Wardoyo, Siswo; Cahyono, Bagus Dwi (The Future of Education Journal, 2025)
This study aims to examine the impact of using video-based e-learning and interactive quizzes on students' understanding of the subject Basic Concepts of Electrical Power at SMKN 1 Ciruas. A quantitative approach was employed using a quasi-experimental design involving two groups of Grade 10 students. The experimental group used e-learning via Moodle, while the control group received conventional instruction. Pre-test and post-test results were analyzed using a t-test. In the experimental group, the average pre-test score increased from 10.55 to 15.23 in the post-test. The paired sample t-test showed a significance value of 0.008 (p < 0.05), indicating a significant effect. The average N-Gain score in the experimental group reached 42.1% (moderate category), whereas the control group only achieved 13.9% (low category), indicating higher effectiveness of the e-learning media. Furthermore, the decrease in standard deviation from 6.73 to 5.67 in the experimental group suggests a more even distribution of student scores and a more consistent improvement in understanding. These findings reinforce that video-based e-learning and interactive quizzes are effective in enhancing student learning outcomes and motivation. This medium is feasible for implementation as a digital learning alternative in vocational schools.